COLLABORATIVE LEARNING IN TERTIARY EDUCATION CLASSROOMS : WHAT DOES IT ENTAIL? (Malaysian Journal of Learning and Instruction, 2023)
Purpose - Collaborative learning has been increasingly recognized as an effective approach to promote students’ success in highereducation. To better understand the factors that contribute to successful collaborative learning, this study applied the Biggs’ presage-processproduct (3P) general model of learning to investigate the role of teaching quality, student-faculty interaction, and relatedness as presage factors, collaborative learning as process factor, and reflective and integrative learning and higher-order thinking as product factors.Methodology - A cross-sectional approach was applied in this study, which included 1,892 Malaysian undergraduates. The study usedthe Quality of University Learning Experience (QULEX) survey to measure various constructs. First, confirmatory factor analysis(CFA) was conducted to establish the psychometric properties of the instruments. Thereafter, structural equation modeling (SEM) wasemployed to evaluate the latent variables relationships.Findings - Based on the findings, collaborative learning fully mediated the prediction of student-faculty interaction, teachingquality, and relatedness on reflective and integrative learning and higher-order thinking.Significance - These findings suggest that collaborative learning with social components and effective teaching maximize students’ learning activities, and they should be fostered in academic institutions to improve students’ academic success. Implications for improving teaching and learning are also discussed in this paper.